Solutions to Assignment 7 • Optional: Calculate the following products of permutations: – (1, 2, 3)(2, 4, 5) = (1, 4, 5, 2, 3) – (3, 4)(1, 2, 3, 4, 5, 6)(4, 3) = (1, 2, 4, 3, 5, 6) – (3, 7)(1, 2, 3, 4, 5, 6)(7, 3) = (1, 2, 7, 4, 5, 6) – (2, 5, 9)−1 (1, 2, 3, 4, 5, 6)(2, 5, 9) = (1, 5, 3, 4, 9, 6) 1. Show that a cycle of length k is odd if k is even and even if k is odd. We can write (a1 , a2 , . . . , ak ) as a product of k − 1 permutations: (a1 , a2 , . . . , ak ) = (a1 , a2 )(a1 , a3 ) . . . (a1 , ak ). If k is even, then k − 1 is odd. If k is odd, then k − 1 is even. 2. Is the permutation (1, 9)(2, 10, 11, 6, 3)(4, 5, 12, 7) ∈ S12 odd or even? Describe a general method to decide whether a product of cycles is odd or even. We can classify each cycle in the product as even or odd using the previous exercise: (1, 9) (2, 10, 11, 6, 3) (4, 5, 12, 7) ∈ S12 . {z } | {z } | {z } | odd even odd Since signature is a homomorphism, sgn((1, 9)(2, 10, 11, 6, 3)(4, 5, 12, 7)) = sgn((1, 9)) sgn((2, 10, 11, 6, 3)) sgn((4, 5, 12, 7)) = −1 · 1 · −1 =1 so the permutation is even. By the same argument, a product of cycles is odd if and only if it contains an odd number of cycles of even length. 3. Suppose that a ∈ Sn and that a = (a1 , . . . , ak ) is a cycle of length k. Show that for all b ∈ Sn , b−1 ab is a cycle of length k. What cycle is it? As suggested by the examples in the optional problem, b−1 ab = (b1 , . . . , bk ), where bi = b(ai ) is the result of applying the permutation b to ai . That is, (b−1 ab)(bi ) = b(a(b−1 (bi ))) = b(a(ai )) = b(ai+1 ) for i < k and (b−1 ab)(bk ) = b(a(b−1 (bk ))) = b(a(ak )) = b(a1 ). If x 6∈ {b1 , . . . , bk }, then b−1 (x) 6∈ {a1 , . . . , ak }, so (b−1 ab)(x) = b(a(b−1 (x))) = b(b−1 (x)) = x. This is the definition of the cycle (b1 , . . . , bk ). 1 4. We label the axes of reflection as follows: V D1 H D2 Then the elements of D8 are D8 = {R0 , R90 , R180 , R270 , D1 , D2 , H, V } and each element corresponds to a map of the square as follows: ρR0 (x, y) = (x, y) ρH (x, y) = (x, −y) ρR90 (x, y) = (−y, x) ρV (x, y) = (−x, y) ρR180 (x, y) = (−x, −y) ρD1 (x, y) = (y, x) ρR270 (x, y) = (y, −x) ρD2 (x, y) = (−y, −x). Then the orbits are: ρR90 (x) = ρV (x) ρR180 (x) = ρD2 (x) x = ρR0 (x) = ρD1 (x) ρR270 (x) = ρH (x) R90 (y) D1 (y) V (y) R0 (y) R180 (y) H(y) D2 (y) R270 (y) R0 (z) = R90 (z) = R180 (z) = R270 (z) = H(z) = V (z) = D1 (z) = D2 (z) 2 and the stabilizers are: Stab(x) = {R0 , D1 } Stab(y) = {R0 } Stab(z) = D8 . Therefore, | Orb(x)| · | Stab(x)| = 4 · |{R0 , D1 }| = 4 · 2 = 8 | Orb(y)| · | Stab(y)| = 8 · |{R0 }| = 8 · 1 = 8 | Orb(z)| · | Stab(z)| = 1 · |D8 | = 1 · 8 = 8 5. Show that H = Stab(0). By definition, Stab(0) = {fm,b | fm,b (0) = 0} = {fm,b | b = 0} = H Show that the left cosets of H are all of the form Suppose that a, b ∈ R and that a 6= 0. Let t = f −1 (0) = −b a . Then fa,b ◦ H = {fa,b ◦ fm,0 | m 6= 0} = {fma,mb | m 6= 0}. On one hand, if fma,mb ∈ fa,b ◦ H, then fma,mb (t) = ma · −b + mb = 0, a so fa,b ◦ H ⊂ Lt . On the other hand, if fa0 ,b0 ∈ Lt , then fa0 ,b0 (t) = 0 a0 t + b0 = 0 b0 a0 = a b 0 so if m = aa , then a0 = ma and b0 = mb. This implies that Lt ⊂ fa,b ◦ H, and every left coset is of the form Lt for some t. Furthermore, Lt = f1,−t ◦ H, so every set Lt is a left coset. 3